2021
DOI: 10.1111/bjir.12612
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the gender job satisfaction paradox: The roots seem to run deep

Abstract: Using the Canadian General Social Survey of 2016, a large nationally representative dataset, this article estimates the gender job satisfaction gap. This unique dataset allows to control for nearly all the variables previously suggested to explain the well-documented higher job satisfaction of women, such as task characteristics, job flexibility and the quality of social relations at work. Accounting for all these variables, the gender gap in favour of women remains in the aggregate sample. But, when the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
(275 reference statements)
1
4
0
Order By: Relevance
“…The research findings contradict the hypothesis put forward. However, they are consistent with an increasing number of studies that report a shrinking gap in job satisfaction between men and women, in this case showing an increase in job satisfaction for men (B€ onte and Krabel, 2014;Corominas Rovira et al, 2012;Dilmaghani, 2022). This situation may be attributed to the higher levels of gender equity that higher education systems around the world have achieved.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The research findings contradict the hypothesis put forward. However, they are consistent with an increasing number of studies that report a shrinking gap in job satisfaction between men and women, in this case showing an increase in job satisfaction for men (B€ onte and Krabel, 2014;Corominas Rovira et al, 2012;Dilmaghani, 2022). This situation may be attributed to the higher levels of gender equity that higher education systems around the world have achieved.…”
Section: Discussionsupporting
confidence: 84%
“…The salary gap between men and women is small at the beginning of their job trajectory but grows rapidly over time. Graduates' age has been related to job satisfaction in studies in Canada (Dilmaghani, 2022) and Argentina (Gallegos Mardones and Campos Requena, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“… 5. This same approach has been applied in similar contexts for the decomposition of the gender gap in different aspects such as job satisfaction (Dilmaghani, 2021). …”
mentioning
confidence: 99%
“…Thus, CIs may impact the degree of work satisfaction depending on whether work tasks rely on communication and hearing ability. Social desirability bias and gender bias may also have impacted outcomes since aggregate data have shown that women typically report higher job satisfaction [ 29 ]. Another aspect that may have influenced the results is that there may be important cultural differences across the included countries that might have played a role in the outcomes.…”
Section: Discussionmentioning
confidence: 99%